Interview Sequences and the Formation of Subjective Assessments - Jonas Radbruch; Amelie Schiprowski (Center for Economic Studies and ifo Institute (CESifo), 2024)
Interviewing is a decisive stage of most processes that match candidates to firms and organizations. This paper studies how and why a candidate's interview outcome depends on the other candidates interviewed by the same evaluator. We use large-scale data from high-stakes admission and hiring processes, where candidates are quasi-randomly assigned to evaluators and time slots. We find that the individual assessment decreases as the quality of other candidates assigned to the same evaluator increases. The influence of the previous candidate stands out, leading to a negative autocorrelation in evaluators' votes of up to 40% and distorting final admission and hiring decisions. Our findings are in line with a contrast effect model where evaluators form a benchmark through associative recall. We assess potential changes in the design of interview processes to mitigate contrasting against the previous candidate.
Keywords: D91; J20; M51; 330; interviews; hiring; contrast effect; memory